Law and Investment Comparison in Australia, South Korea, and Indonesia - Montayana Meher; Ningrum Natasya Sirait; Mahmuddin (Faculty of Law, Universitas Pekalongan, 2025)
This essay examines the legal and policy frameworks regulating foreign direct investment (FDI) in Australia, South Korea, and Indonesia by focusing on three key areas of law: national laws on foreign investment (including treaties), competition and consumer law, and anti-corruption law. These legal domains significantly influence the decisions and risk assessments of outbound investors. The study highlights how each country’s legal system—Australia’s common law versus South Korea’s and Indonesia’s civil law traditions—affects FDI regulation. It also contrasts developed (Australia and South Korea) and developing (Indonesia) economies, revealing distinct challenges and opportunities in attracting sustainable FDI. Comparative legal analysis is used to assess the effectiveness and limitations of existing frameworks, especially in the context of pre- and post-pandemic reforms. While Australia and South Korea are seen as stable and secure environments for investment, Indonesia, despite being high-risk, offers potentially higher returns. The essay argues that legal clarity and effective governance—especially in anti-corruption and competition regulation—play a critical role in fostering investor confidence. Using a normative legal research method with descriptive, analytical, and case study approaches, the essay concludes that comprehensive understanding of these legal areas is essential for minimizing investment risks and promoting sustainable FDI flows.